TREATMENT OUTCOMES OF GESTATIONAL TROPHOBLASTIC DISEASE, EXPERIENCE FROM SAUDI ARABIA - Latif, Muhammad Farooq; Azam, Faisal; Tirmazy, Syed Hammad Hassan; Bukhari, Nedal (Journal of Ayub Medical College Abbottabad, 2024)
Background: This research aims to assess the treatment outcomes and chemotherapy duration required for the normalization of Human chorionic gonadotropin (HCG) levels in patients diagnosed with Gestational Trophoblastic Neoplasia (GTN), encompassing both benign and malignant forms of the condition. Methods: This retrospective study included GTD patients treated with chemotherapy in a single oncology clinic from January 2016 to May 2022. Clinical data were gathered from electronic records of the patients. Results: During the study period, a total of 24 patients diagnosed with GTD underwent chemotherapy, with a median age of 32 years (range: 18-51). Intramuscular Methotrexate was the primary single-agent chemotherapy utilized in 20 cases (83%) for low-risk disease, while the EMA-CO regimen was the predominant combination chemotherapy employed in 3 cases (13%) for high-risk disease. The median number of chemotherapy cycles administered was 2 (range: 1-16), with a median duration of 4 weeks (range: 1-16) required for Human chorionic gonadotropin (HCG) normalization. Approximately half of the patients (n=10, 47.5%) transitioned to second-line combination chemotherapy, with a median normalization duration of 4 months. Four patients (40%) subsequently received third-line combination chemotherapy using the EMA-CO regimen. Initial complete response was achieved in 11 patients (47%) with first-line treatment, while 10 patients (43%) required second-line chemotherapy and 4 patients (17%) necessitated third-line EMACO chemotherapy. Of the 24 patients, 22 achieved complete response, while 2 patients are currently undergoing treatment. Conclusion: All patients successfully attained complete response with chemotherapy. The median duration of chemotherapy for achieving normalization of HCG was 4 weeks, equivalent to 2 cycles. Notably, only 4 patients necessitated third-line chemotherapy following single-agent chemotherapy in the first and second lines.